2015
DOI: 10.1007/3418_2015_110
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Catalyzed Carboxylation of Organic Substrates with Carbon Dioxide

Abstract: The development of sustainable chemical processes is a long-standing challenge. Carbon dioxide represents a renewable C1 building block for organic synthesis and industrial applications as an alternative to other common feedstocks which are based on natural gas, petroleum oil, or coal. Apart from the advantages associated with the nontoxicity and abundance of CO 2 , its utilization further enables the reduction in its atmospheric content, which contributes significantly to the greenhouse effect. Although wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 178 publications
(224 reference statements)
0
4
0
Order By: Relevance
“…To our surprise, the palladium- and silver-mediated decarboxylation processes all require insurmountable barriers (Figures S17 and S18). Instead, we discovered that deprotonated penta-arylated products can undergo facile decarboxylation without any additional reagent (Table ). With R = Ph ( 3a ), the decarboxylation barrier is only 13.6 kcal/mol, and the reaction is exergonic with Δ G solv = −0.5 kcal/mol (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…To our surprise, the palladium- and silver-mediated decarboxylation processes all require insurmountable barriers (Figures S17 and S18). Instead, we discovered that deprotonated penta-arylated products can undergo facile decarboxylation without any additional reagent (Table ). With R = Ph ( 3a ), the decarboxylation barrier is only 13.6 kcal/mol, and the reaction is exergonic with Δ G solv = −0.5 kcal/mol (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order for monoortho-substituted benzoic acids 28 and less electron rich benzoic acids 29 to undergo decarboxylation a stoichiometric amount of palladium was required (Scheme 6). 26 Mechanistic studies by various groups 14 have shown a very distinct reaction profile for the palladium system compared to those for copper and silver; firstly the decarboxylation proceeds through a 4-membered transition state with no interaction with the carboxyl carbon (see 31 vs. 8 and 19, Scheme 7).…”
Section: Methodsmentioning
confidence: 99%
“…While a significant step-forward, such a method is not particularly step-economical and requires handling with stoichiometric and, in many instances, air-sensitive organometallic species, thus reinforcing a change in strategy. Although the recent years have witnessed the discovery of a myriad of elegant catalytic reductive carboxylation techniques with organic (pseudo)halides [13][14][15][16], the utilization of unsaturated hydrocarbon counterparts constitutes an ideal platform in the carboxylation arena, as these motifs can be obtained in bulk from our petrochemical industry, thus representing a formidable and unique opportunity for converting raw materials into valuable products at the industrial level [17]. Additionally, such a scenario would allow for accessing carboxylic acids at a large scale while avoiding the utilization of toxic carbon monoxide [11].…”
Section: Introductionmentioning
confidence: 99%